The marble façade of the Ducal Palace of Vila Viçosa in the context of the 1940 Centenary Commemorations: cleaning and consolidation - Soares, Clara Moura (2021)
Espera realização de congresso "Consolidation 2021. Stone Consolidation in Cultural Heritage" (20-22 outubro 2021). [Apoio FCT (ref.UIDB/04189/2020)]